Metaphors in Iraqi Media Discourse: Newspaper Headlines as a Case Study - Hayder Tuama Jasim Al-Saedi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The current study investigates the conceptual metaphorical expressions in news discourse (newspapers headlines) and how they are constructed to shed the light on the Iraqi affairs metaphorically. The researcher tries to find answers on how the metaphors represented the sociopolitical and economic issues, how they were addressed metaphorically in the Iraqi newspapers headlines, and what the common conceptual source domains that addressed these issues. The researcher adopted the Conceptual Metaphor Theory (CMT) by Lakoff and Johnson (1980) to investigate and classify the dominant source domains in the Iraqi newspapers headlines. Data are the headlines that gathered from the Iraqi daily newspapers in Arabic and are translated to English literally. The researcher used the Metaphorical Identification Procedure (MIP) by Pragglejaz Group (2007) to identify the lexical units that are metaphorical to extract the contextual meanings of these units and how they function to be metaphorical. The results revealed that the journalists used different conceptual source domains in the Iraqi newspapers headlines; they are FIRE, HEAT, ANIMAL, FOOD, GAME, and BIRTH metaphors to convey different target domains that focused on the Iraqi sociopolitical and economic issues. The study concluded that the metaphors are used pervasively in the Iraqi newspapers headlines to shed the light on different cases in the Iraqi daily life talks and the common and dominant source domain is the concept of ANIMAL Metaphor.